The fabrication and testing of chitosan-lignin composites - Ong, Ding Yi. (2010)
Lignin, one of the most abundant natural polymers, has been employed to fabricate a composite fiber with chitosan, another abundant natural polymer. Lignin is known for its toughness whereas chitosan is known for its versatility in forming composites. Therefore, the investigation of forming fibers from cheap resources, which result in the enhancement of the mechanical properties, is of great interest. This project carried out studies to explore the outcome of various concentration of lignin on the maximum stress, maximum strain, modulus of elasticity and toughness of the composite fibers formed. The synthesis of the composite fibers will be done using wet-spinning method at concentration (w/w %) of 1%, 3%, 5%, 7% and 9% of Lignin 1(lignin, alkali) and Lignin 2 (lignin, alkali, low sulfonate content). The effects of the mechanical strength of the chitosan-lignin composite will be examined and compared using the tensile testing equipment. The tensile test exhibits superior mechanical properties at 3% Lignin 1/Chitosan composite and 3% Lignin 2/Chitosan composite as compared to the pure chitosan. However with increasing concentration of lignin, the mechanical properties shows a declining trend. A further comparison reveals that the 3% Lignin 1/Chitosan composite exhibits better mechanical properties than the 3% Lignin 2/Chitosan composite.